A simple method to improve the performance of perovskite light-emitting diodes via layer-by-layer spin-coating CsPbBr3 quantum dots. Issue 48 (31st July 2018) - Li, Bobo; Li, Xiaomeng; Li, Xia; Liu, Haolin; Li, Zhaonan; Xiang, Guohong; Liu, Yuhan; Zhou, Taojie; Fang, Xuan; Zhang, Zhaoyu
Abstract : Schematic diagram of perovskite LEDs and EQE–voltage curves of these devices. Abstract : Recently, all-inorganic halide perovskite quantum dots have become a very promising material for light-emitting diodes. Herein, we demonstrate a facile method, namely, layer-by-layer spin-coating of CsPbBr3 QDs to improve device performance. After optimization of the number of emissive layers, the maximum EQE can be increased from an initial value of 0.69% to 2.31%. Additionally, we inserted a CBP layer between PEDOT:PSS and CsPbBr3 multilayers to balance charge transportation and recombination. As a result, a 37% improvement in EQE (up to 3.16%) and highest luminance of 2629 cd m −2 are obtained.